Calpain-10 and insulin resistance in human skeletal muscle - Norton, Luke (2007)
Variation in the calpain-10 gene has been linked to a three-fold increased risk for type 2 diabetes in Pima Indian and some European populations. Furthermore, reduced skeletal muscle expression of calpain-10 is associated with reduced insulin mediated glucose disposal and carbohydrate oxidation. The skeletal muscle specific calpain-3 plays a key role in skeletal muscle integrity and has also been linked to insulin resistance in humans and rodents.